Distribution of special education programs in mainstream schools in Selangor - Mohamed Osman, Mariana; Ahmad Suhaimi, Ainul Ashiqin; Rabe, Noor Suzilawati (American Scientific Publishers, 2017)
The Integrated Special Education Program (PPKI) is a special education program that offers education for pupils with learning disabilities, hearing impairment and sight impairment. The objectives of this paper are to highlight the distribution and the location of schools with PPKI classes in the state of Selangor as well as the number of pupils in PPKI classes according to its classification. Data collected is based on documents and related sources from the Special Education Unit of the State Education Department. All PPKI classes are integrated into mainstream public schools; however, not all mainstream public schools offer PPKI classes, which results in the difference in the number of mainstream public schools and public schools with PPKI. There are 209 PPKI schools inclusive of both primary and secondary schools in the state of Selangor. The findings reveal that the three types of PPKI classes are not evenly distributed throughout the districts. PPKI schools are also not as well located as mainstream schools because there is no defined suitable location for Special Education facilities unlike the school location guidelines for primary and secondary mainstream schools.